Tropical Diabetic Hand Syndrome: report of 2 cases - Ewezu Ngim, Ngim (The African Field Epidemiology Network, 2012)
Diabetes mellitus is known to be complicated by foot lesions. However, a few cases of hand complications have been reported in some parts of the world. The case notes of two patients who presented with this condition in our hospital were retrieved and relevant information extracted. The cases of diabetic hand complications seen in our centre are here reported to draw the attention of medical practitioners to the occurrence of this potentially debilitating and occasionally fatal condition. Appropriate counselling of diabetic patients on hand care strategies and good glycemic control are important preventive measures.